The Influence of Competence and Motivation on Employees Performance - Dewanta Fachrureza; M. Liga Suryadana (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
The purpose of this study was to find out and obtain the data and analyze the data that reinforces the notion above for applicative solutions or can be done to solve the problem is happening. In this study the authors used a quantitative approach. housekeeping employees take a sample and use the questionnaire as a method of data collection. The reason researchers used a quantitative approach because the researcher intends to eliminate subjectivity in research. The results obtained do indeed proved strong motivation and competence contribute to the performance of the employee. Each variable has a strong influence signifies the alleged author approached correctly. Based on the data also that the competence and motivation is weak then performance will be less. Recommendations from this research is to use the award or awards system to boost employee motivation and also conduct training for employees to improve knowledge, skills and attitudes.